(untitled) (Eurasian Medical Research Periodical, 2022)
For the study, 50 women diagnosed with alcoholism and treated at the Samarkand Regional Narcology Hospital were selected. The main prognostic criteria for the course of alcoholism were studied: hereditary burden of alcoholism and affective psychoses, personality psychopathy and motive for alcohol abuse, age of onset. The following were identified as prognostic criteria for alcoholism: low prevalence of hereditary predisposition to alcoholism, the presence of hysterical, hypothymic, and anxious symptoms that do not go beyond emphasis. Alcohol abuse begins after the age of 25, recurrence of alcoholism associated with traumatic situations, and living alone are the main factors that lead to the development of alcoholism in women